(untitled) (Baghdad Science Journal, 2012)
This study were implemented on (60) broiler chick with one day age divided into three equal groups , first one was given basal diet while group two and three given adiet contain 0.01% ,0.02% tryptophan respectively for 7 weeks . The results show that the chicks recevd the tryptophan have asigneficant increasment in hemoglobin concentration, red blood cells count, packed cell volume and increased the level of globuline concentration and lymphocyte % which mean that the addition of tryptophan improve blood picture charactores and the immunity of the broiler chickens and this evident from the good health state and decrease the mortality among birds .